Suppression of Nearest Neighbour Electron Hopping in FeSe-Based Superconductors - Pustovit, Yu.V.; Kordyuk, O.A. (Металлофизика и новейшие технологии, 2018)
In this paper, we evaluate the fitting parameters for the hopping model for the dxy and dxz bands within the Γ–M cut for different FeSe-based superconductors. Comparison of these parameters for DFT calculations and for experimentally obtained data reveals a dramatic change of hopping probability between the nearest neighbours. This change is much bigger than the expected band renormalization and can be explained by the appearance of an antiferromagnetic-like ordering. В статье оценены параметры модели перескоков для аппроксимации dxy- и dxz-зон в Γ–M-сечении для разных сверхпроводников на основе FeSe. Сравнение значений параметров для экспериментально полученных электронных дисперсий и рассчитанных с помощью метода ТФП показало снижение вероятности перескоков между ближайшими соседями. Такие изменения можно объяснить возникновением некоторого упорядочения. У статті оцінено параметри моделю перескоків для апроксимації dxy- та dxz-зон у Γ–M-перерізі для різних надпровідників на основі FeSe. Порівняння значень цих параметрів для експериментально одержаних і розрахованих методою ТФГ електронних дисперсій показує зменшення ймовірности перескоку між найближчими сусідами. Такі зміни можуть бути пояснені появою певного виду впорядкування.